Pharmaceutical Residues in Sediments of a Coastal Lagoon in Northwest Mexico—Occurrence and Environmental Risk Assessment - Oscar Fernando Becerra-Rueda; Griselda Margarita Rodríguez-Figueroa; Ana Judith Marmolejo-Rodríguez; Sergio Aguíñiga-García; Juan Carlos Durán-Álvarez (Journal of Xenobiotics)
Contamination of marine ecosystems by pharmaceutically active compounds (PhACs) deserves more research since their environmental fate differs from that observed in freshwater systems. However, knowledge remains scarce, especially in semi-arid coastal regions of the Global South. This study investigates the occurrence and distribution of caffeine, carbamazepine, ciprofloxacin, and sulfamethoxazole in sediments from the La Paz lagoon, a coastal system in a semi-arid region of Mexico with inverse estuarine conditions. Samples of superficial sediments (0–5 cm depth) were collected from 18 sampling points distributed through the lagoon, encompassing sites heavily polluted by discharges of municipal sewage and 3 potentially pristine sites far from the urban and peri-urban zones. Also, a 25 cm length sediment core was taken and divided into 1 cm sub-samples to determine the deposition of target PhACs in the sediment bed through time. The extraction of the target PhACs was performed through the accelerated solvent extraction (ASE) technique and quantification was achieved using a validated HPLC-MS/MS analytical method. The concentration of caffeine, carbamazepine, ciprofloxacin, and sulfamethoxazole in superficial sediment oscillated in the range of 1 to 45 ng g−1 (dry weight). The highest mass fraction of target PhACs was detected in sites impacted by wastewater discharges. The caffeine-to-carbamazepine ratio was determined for the first time in marine sediments impacted by wastewater discharges, resulting in values from 4.2 to 9.12. Analysis of the 25 cm length sediment core revealed a high dispersion of caffeine, which was attributed to high water solubility, while antibiotics were predominantly detected in the upper 20 cm of the core. Risk quotients were calculated, observing low risk for caffeine, carbamazepine, and ciprofloxacin, while sulfamethoxazole presented high risk in all the sampling points. PhACs are retained in superficial sediments from a lagoon impacted by wastewater discharges, and the level of impact depends on the properties of the compounds and the TOC content in sediments. Risk assessments should be performed in the future considering the combination of pharmaceuticals and byproducts in marine sediments. This research emphasizes the importance of sewage management in preserving marine ecosystems in semi-arid regions in the Global South.